X-ray and lensing mass estimates in galaxy clusters - Donnarumma, Annamaria <1981> (Alma Mater Studiorum - Università di Bologna, 2010)
In this Thesis we have presented our work on the analysis of galaxy clusters through their X-ray emission and the gravitational lensing effect that they induce. Our research work was mainly finalised to verify and possibly explain the observed mismatch between the galaxy cluster mass distributions estimated through two of the most promising techniques, i.e. the X-ray and the gravitational lensing analyses. Moreover, it is an established evidence that combined, multi-wavelength analyses are extremely effective in addressing and explaining the open issues in astronomy: however, in order to follow this approach, it is crucial to test the reliability and the limitations of the individual analysis techniques. In this Thesis we also assessed the impact of some factors that could affect both the X-ray and the strong lensing analyses.